Propensities to make attributions to prejudice and (mis)perceptions of racism in the context of police shootings. (November 2021) - Miller, Stuart S.; Peacock, Navanté K.; Saucier, Donald A.
Abstract: We examined whether individual differences in tendencies to perceive prejudice are related to the (mis)perception of racial discrimination. Participants were presented with either strong or weak evidence of racism in a scenario involving a White police officer shooting a Black man. Lower levels of tendencies to perceive prejudice were related to underperceiving racism when the evidence was strong. However, we found no evidence that higher levels of tendencies to perceive prejudice were related to overperceiving racism when the evidence was weak. These findings suggest believing racial prejudice is uncommon creates more biased perceptions of racism than believing prejudice is pervasive. Highlights: Lower tendencies to perceive prejudice were related to underperceiving racism Higher tendencies to perceive prejudice were not related to overperceiving racism Thus, biased perceptions of racism appear to be limited to the denial of racism